Health Communication and Behavioural Practice towards Ending Hepatitis B Virus in Southwest Nigeria - Evaristus Adesina; Davies Adeloye; Hezekiah Falola; Babatunde Adeyeye; Darlynton Yartey; Tolulope Kayode-Adedeji (The Scientific World Journal)
Responding to the international call for strategic information to understand viral hepatitis, this study investigated the health communication practice on hepatitis B virus in Southwest Nigeria. Existing studies on HBV in Nigeria have primarily concentrated on health practitioners and their patients while neglecting detailed empirical data on semiurban and urban demographic information. This study examines health communication channels as predictors of knowledge, attitude, and behavioural practices with an emphasis on three Southwest states (Lagos, Oyo, and Ogun) in Nigeria that have the highest prevalence rate of HBV. Data were gathered through a survey from a total of 600 respondents of Southwest Nigeria randomly selected through the multistage sampling technique. The hypotheses were tested with the use of multiple regression. The result reveals that health communication channels for hepatitis B virus management had a significant influence on knowledge (F = 12.708, Df = 581, P<0.05, Sig. at 0.000), attitude (F = 3.430, Df = 581, P<0.05, Sig. at 0.000), and preventive practices (F = 11.075, Df = 581, P<0.05, Sig. at 0.000) of residents of Southwest Nigeria, respectively. The study concludes that health communication channels such as the television, Internet, radio, newspaper, and health workers positively influence the behavioural practices of residents of Southwest Nigeria. The study recommends the development of a nationwide communication system on HBV targeted at putting an end to the disease in line with the 2030 global elimination objective of Sustainable Development Goal 3.